2016
DOI: 10.1182/blood-2016-06-724732
|View full text |Cite
|
Sign up to set email alerts
|

Antigen modulation as a potential mechanism of anti-KEL immunoprophylaxis in mice

Abstract: In contrast, transfused RBCs with the KEL glycoprotein antigen fully intact continued to circulate for days in double-KO mice despite treatment with immunoprophylaxis. Further, in vitro phagocytosis assays showed no consumption of opsonized murine RBCs by double-KO splenocytes. Taken in combination, our data suggest that modulation of the KEL antigen (and potentially RBC clearance) by redundant recipient pathways involving both FcgRs and C3 may be critical to the mechanism of action of polyclonal anti-KEL immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 37 publications
3
64
0
Order By: Relevance
“…21 In conclusion, whereas high-affinity alleles encoding FcgRs, which are known to influence the clearance of anti-D-sensitized red cells 12 are indeed associated with a severe course of HDFN, they do not seem to influence the preventive effect of Rh-Ig. This observation is in agreement with results of recent studies in mouse models on antibodymediated suppression of RBC alloimmunization, in which prevention of response occurred independent of RBC clearance rate 22,23 A recent murine study suggested that antigen modulation might play a role in immunoprophylaxis 24 ; however, FcgR polymorphisms influencing antigen modulation have not been identified to date. 25 Altogether, these observations indicate that the mechanism of action of RhIG differs from the mechanism of action of maternal anti-D. At this time, recombinant antibodies aimed to replace polyclonal plasma-derived Rh-Ig are selected on their ability to clear RBC.…”
supporting
confidence: 91%
“…21 In conclusion, whereas high-affinity alleles encoding FcgRs, which are known to influence the clearance of anti-D-sensitized red cells 12 are indeed associated with a severe course of HDFN, they do not seem to influence the preventive effect of Rh-Ig. This observation is in agreement with results of recent studies in mouse models on antibodymediated suppression of RBC alloimmunization, in which prevention of response occurred independent of RBC clearance rate 22,23 A recent murine study suggested that antigen modulation might play a role in immunoprophylaxis 24 ; however, FcgR polymorphisms influencing antigen modulation have not been identified to date. 25 Altogether, these observations indicate that the mechanism of action of RhIG differs from the mechanism of action of maternal anti-D. At this time, recombinant antibodies aimed to replace polyclonal plasma-derived Rh-Ig are selected on their ability to clear RBC.…”
supporting
confidence: 91%
“…[27][28][29][30] We found that DHbA was higher in the patients with splenomegaly while lower in patients with splenectomy, demonstrating variability in the rate of RBC clearance by the reticuloendothelial system during CTT. [31][32][33] Further, we demonstrated that DHbA does directly impact CTT outcomes, as increased HbA clearance leads to lower pretransfusion Hb, higher HbS, and higher reticulocytes. Although the factors that dictate RBC alloimmunization continue to be an area of active investigation, [34][35][36][37][38][39] as patients with RBC antibodies have increased HbA clearance, it is possible that increased removal of transfused RBCs may reflect increased RBC uptake by immune cells that are uniquely poised to facilitate RBC alloimmunization.…”
Section: Discussionmentioning
confidence: 63%
“…In patients with decreased survival of transfused RBCs, it is possible that nonhumoral immune responses or evanescent antibodies that are undetected by antibody‐screening techniques have a role in facilitating RBCs clearance, as evidenced by high proportions of delayed HTRs with undetectable antibodies . We found that ΔHbA was higher in the patients with splenomegaly while lower in patients with splenectomy, demonstrating variability in the rate of RBC clearance by the reticuloendothelial system during CTT . Further, we demonstrated that ΔHbA does directly impact CTT outcomes, as increased HbA clearance leads to lower pretransfusion Hb, higher HbS, and higher reticulocytes.…”
Section: Discussionmentioning
confidence: 67%
“…Although several studies have previously addressed the possible mechanisms of action of RhIG, the exact mechanism(s) remain unclear . Whereas the antigen masking or steric hindrance hypothesis appears to be the prevailing mechanism in the antibody‐mediated immune suppression model with sheep RBCs in mice, this mechanism insufficiently explains RhIG function in humans, based on the low level of opsonization sufficient to exert suppression .…”
Section: Discussionmentioning
confidence: 72%
“…Although several studies have previously addressed the possible mechanisms of action of RhIG, the exact mechanism(s) remain unclear. [11][12][13]24,25 Whereas the antigen masking or steric hindrance hypothesis appears to be the prevailing mechanism in the antibody-mediated immune suppression model with sheep RBCs in mice, 26 this mechanism insufficiently explains RhIG function in humans, based on the low level of opsonization sufficient to exert suppression. [9][10][11] Furthermore, antigen masking is an antigen-specific mechanism and if this was the main explanation for RhIG function, it would not prevent development of other RBC alloantibody specificities as found in our study.…”
Section: Discussionmentioning
confidence: 99%